Eksplorasi Senyawa dan Efek Ekstrak Daun Sirsak (Annona muricata L.) terhadap Viabilitas dan Ekspresi Gen BCL2 pada Sel HeLa - Jasmin Ayla Fitri Daulay; Hanifa Tasya Kamila; Rahma Yulia; Nadila Ananda Putri (Universitas Muhamadiyah Manado, 2026)
Human Papillomavirus (HPV) infection is typically the cause of cervical cancer, one of the cancers with a high death rate among women. Despite their widespread use, conventional therapeutic approaches still have drawbacks, such as the emergence of cancer cell resistance and severe side effects. Natural compounds are now used as safer alternative treatments as a result. Soursop leaves (Annona muricata L.) are one plant that has been shown to have anticancer potential. Through phytochemical screening, compound identification using GC-MS, cell viability testing using the MTT Assay, and BCL2 gene expression analysis using qPCR, this study attempts to examine the potential of soursop leaf extract as an anticancer agent against cervical cancer cells (HeLa cells). The results of the phytochemical examination showed that steroids, phenolics, and alkaloids were present. Ostole, bisacumol, and ricinoleic acid were found to be the predominant components when the active chemicals were identified by GC-MS. With an IC²₀ value of 5.01 μg/mL, the MTT experiment demonstrated that soursop leaf extract could decrease cell viability as the concentration rose. Furthermore, BCL2 gene expression was significantly reduced, especially in treatments with doses of 500 and 1000 μg/mL, according to the results of qPCR gene expression analysis. The overall findings suggest that soursop leaf extract may be used as a natural anticancer treatment against HeLa cells by lowering the expression of the BCL2 gene.